CHANGES TO THE RED SNAPPER FISHERIES IN THE ARAFURA SEA FISHERIES MANAGEMENT AREA - Siti Nuraini; Tri Ernawati (Research Center for Fisheries, 2009)
Red snappers are target species and exploited by industrial fisheries off the Bottom longline, trap and as by product of fish net in Arafura Sea. This study proposed to identify effect of industrial fishing on red snapper fishery; on size and catch composition.